Analysis of the Effects of Climate Changes on the Iraqi Economy - Ilham Waheed Dahham (Zanco Journal of Humanity Sciences)
Iraq faces the real challenges of being affected by the consequences of climate change with the deterioration of weather and environmental degradation, as well as growing population, which is putting increasing pressure on natural resources, which have become scarcer and away from the state of environmental sustainability. In addition to the issues of reconstruction after the wars, conflicts and conflicts experienced by the country, the research seeks to monitor the relationship between climate change and the economic and social effects of this change in Iraq, and analyze the effects of climate change on the Iraqi economy. The research found that climate change will adversely affect sectors of the national economy and hence economic development plans.